1999
DOI: 10.1046/j.1365-2036.1999.00555.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of Helicobacter pylori eradication therapy—the impact of antimicrobial resistance on eradication rates

Abstract: The cure rate with most regimens dropped significantly, in case of nitroimidazole-resistant strains, compared to nitroimidazole-susceptible strains. In case of clarithromycin resistance, the efficacy of most regimens is also decreased; however, data are still scarce. These data should allow physicians to make a better choice of an appropriate therapy for their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
266
2
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(284 citation statements)
references
References 39 publications
7
266
2
5
Order By: Relevance
“…Trichomonas vaginalis, Entamoeba histolytica, Enterococcus species, Giardia lamblia, Clostridium species, and Bacteroides (1)(2)(3)(4) and is also a critical ingredient of modern multidrug therapies for Helicobacter pylori eradication regimes used to control ulcers (5). The mode of action for the 5-Ni antibiotics, as illustrated in Fig.…”
Section: Dimetridazole (Dmz) and Tinidazole (Tnz) Mtr Is Extensivelmentioning
confidence: 99%
“…Trichomonas vaginalis, Entamoeba histolytica, Enterococcus species, Giardia lamblia, Clostridium species, and Bacteroides (1)(2)(3)(4) and is also a critical ingredient of modern multidrug therapies for Helicobacter pylori eradication regimes used to control ulcers (5). The mode of action for the 5-Ni antibiotics, as illustrated in Fig.…”
Section: Dimetridazole (Dmz) and Tinidazole (Tnz) Mtr Is Extensivelmentioning
confidence: 99%
“…Production of biofilm by H. pylori has important effect in promoting its resistance to antimicrobials and host defense factors [40]. It is generally accepted that the H. pylori dormant states of coccoid forms can survive for a long time in the gastric environment.…”
Section: Discussionmentioning
confidence: 99%
“…The higher rates of metronidazole resistance in Brazil can be due its widespread use in gynecological infections and parasitic diseases like giardiasis and amebiasis (27) . In a review of all available data in the literature including 770 studyarms, HOUBEN et al (10) observed that in the case of nitroimidazole resistance, a drop in efficacy of up to 50% was found for bismuthbased triple and proton pump inhibitor-based triple therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, caution is required when using the 1.5 g/day dosage owing to the risk of severe, life-threatening pseudomembranous colitis, particularly in the elderly (28) . One-week low-dose clarithromycin (250 mg bid) combinations with PPIs and tinidazole or metronidazole have also been tested and have achieved impressive (93%-95%) eradication rates (10,15,16) . However, the 30%-40% prevalence of metronidazoleresistant Hp strains in the United Kingdom, Belgium, Finland, and other industrialized countries (9,17,31) casts doubt on the reproducibility of such results in the general population.…”
Section: Discussionmentioning
confidence: 99%